Aerial Journey from Portugal to Timor, Macau, India, and Return (1934) - Neves, Fernando M. S. P. (2021)
In the 1920s and 1930s, a group of Portuguese Aviation Pioneers added the name of Portugal to the History of Aviation, essentially by performing Aerial Journeys to Portuguese Colonies. East Timor was an outlier until 1934. Thus, Humberto Amaral da Cruz conceived and designed an Aerial Journey from Portugal to East Timor, Macau, India, and return, with the primary purpose to highlight the country's relevance and consolidation as a colonial power as a demonstration of sovereignty over its most distant domains. With the help of a national public subscription, a government subsidy, and the support of some private entities, he purchases a De Havilland DH. 85 aircraft. Between October 25 and December 21, the pilot, and his mechanic, António Lobato, accomplish their Journey of 42,670 km in 268 hours and 25 minutes. The pilots' reception was apotheotic, with enormous national pride, followed by the feeling of dignity and expansion of the Portuguese Nation. The Journey had a global impact through the massive propaganda effort from distant countries in the Far East and a vast national influence through the rapprochement and consolidation of the Portuguese colonial empire in the most remote places in the World. Humberto da Cruz demonstrated his skills as a pilot, his skill as an officer, and the strength of his upstanding character. In particular, he praised aviation for developing a new era on earth, arguing that Portugal would have to adopt this form of communication between its overseas territories, Brazil, and the rest of the World.